Peningkatan Mutu Pendidikan melalui Strategi Implementasi Manajemen Berbasis Madrasah - Fatahilah Fatahilah (Departement of Mathematics Education, 2024)
Education is one of the efforts that really requires serious and consistent attention from all stakeholders ranging from education stakeholders both government, community, parents, educators, education, school principals and madrasah committees. This study wants to know the improvement of the quality of education in Madrasah Tsanawiyah Negeri, know the implementation strategy of Madrasah-based management and use Qualitative descriptive research methods by using data and fact collection techniques through interviews, observations and documentation. From the results of the study, it is known that improving the quality of education through this Madrasah-based management implementation strategy is very effective and efficient. The thought contribution from this research is in the form of input to all stakeholders in Madrash and the Ministry of Religious Affairs, so that the implementation strategy of Madrasah-based management will be further improved. So that in the future the quality of education will be more advanced, better and can compete with other state madrassahs.